Reason, Revelation, and Sufism: The Epistemic Paradigm of al-Ghazali and Ibnu Taimiyyah - Hamdan Maghribi; Alfina Hidayah (Center of Islamic and Occidental Studies, 2025)
This article examines the construction of Sufi epistemology according to two major Islamic thinkers: Abu Hamid al-Ghazali and Ahmad ibn Taimiyyah. These figures represent contrasting poles in Islamic intellectual history—al-Ghazali as a defender and reformer of syarī‘ah-based Sunni Sufism, and Ibnu Taimiyyah as a sharp critic of Sufism influenced by speculative theology and philosophy. The study explores their views on the sources, methods, and validity of Sufi knowledge, particularly regarding maqām, aḥwāl, kasyf, ilhām, and ma‘rifah, as well as their perspectives on the relationship between reason, revelation, and intuition (dzawq) as epistemic pathways. This research is qualitative in nature, with literature study, and historical-philosophical approach. The authors examine the primary works of both figures and compares them through a chronological and systematic framework. It allows for an exploration of the sociocultural and theological contexts that shaped their epistemological constructions. The study finds that al-Ghazali integrates rational inquiry (syahādah al-‘aql) with inner illumination (kashf), framing ma‘rifah as the product of synergy between tazkiyah al-nafs and tajallī ilāhī. He legitimizes intuitive knowledge as long as it remains within the bounds of the syarī‘ah. Ibnu Taimiyyah, while acknowledging ilhām and kasyf among the saints (awliyā’), restricts their epistemic validity to the limits of nash and fithrah, rejecting any claim that spiritual experience can supersede revelation. Despite their differing approaches, both uphold syarī‘ah-rooted spirituality and reject speculative excesses that threaten the foundations of tawḥīd.